A novel brittleness evaluation method for shale based on nonlinear weighting of mineral composition: a case study of the Qiongzhusi formation in southwestern Sichuan Basin - Wang, Wenhao; Xie, Weibiao; Ma, Haili; Ren, Zilong; Yin, Qiuli; Zhang, Pan (Frontiers in Earth Science, 2026)
Accurate assessment of shale brittleness is crucial for identifying optimal development zones, directly impacting the effectiveness of fracturing stimulation and production forecasting. To address the ambiguity regarding the influence of different mineral components on brittleness in current mineral-based evaluation approaches, this study employs the Analytic Hierarchy Process (AHP) to quantify the brittleness contribution coefficients of diverse minerals based on their distinct physical properties. Moreover, the study considers the nonlinear correlation between mineral content and shale brittleness to enhance the existing mineral-based brittleness index model. Application of this refined model to the Qiongzhusi Formation shale in the southwestern Sichuan Basin reveals a reduction of approximately 34% in the mean relative error compared to traditional methods, demonstrating improved capture of vertical brittleness variations. This model effectively characterizes the vertical variability of shale reservoir brittleness, offering a straightforward construction process, broad applicability, and essential data support for subsequent comprehensive geological and engineering assessments.